Transient heating of a rotating elastic-plastic solid shaft - Arslan, E.; Mack, W.; Eraslan, A. N. (Proceedings in applied mathematics and mechanics, 2008)
Based on Tresca's yield criterion and the flow rule associated with it, the transient plasticization in a rotating elastic–plastic solid shaft with temperature dependent yield stress subject to a temperature cycle is studied. Special attention is paid to the residual stresses. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)